Big Data Analytics Capabilities and Firm Competitiveness in The Digital Age: A Socio-Economic Perspective from Emerging Markets - Mayndarto, Eko Cahyo (Baileo: Jurnal Sosial Humaniora, 2025)
This article examines the role of Big Data Analytics Capabilities (BDAC) in enhancing firm competitiveness in the digital era, with a specific focus on socio-economic perspectives in emerging markets. Driven by increasing business complexity and rapid technological advancement, firms are compelled to treat data as a strategic asset for decision-making. This study adopts a literature review method, analyzing prior empirical findings, theoretical frameworks, and scholarly references to explore how BDAC influences organizational performance and competitive advantage. The findings indicate that BDAC positively contributes to innovation, operational efficiency, and the attainment of competitive advantage. Key enablers of BDAC include technological infrastructure, data analytics skills among human resources, and a data-driven organizational culture. Furthermore, dynamic capabilities serve as a critical mediator that enhances the impact of BDAC, while external environmental dynamism acts as a moderating factor influencing its effectiveness. This study offers novel insights by emphasizing the importance of integrating internal and external factors in developing data-driven business strategies. The main recommendation is the continuous strengthening of BDAC as a core component of long-term strategic planning to achieve sustainable competitiveness. This article contributes to the social sciences and humanities literature by shedding light on the implications of digital transformation for organizational dynamics and strategic development in emerging economies.